2019
DOI: 10.1051/bioconf/20191504001
|View full text |Cite
|
Sign up to set email alerts
|

Total content of phenols and antioxidant activity of grape skins and seeds cabernet sauvignon cultivated in Valle de Guadalupe, Baja California, México

Abstract: The evaluation of the antioxidant capacity of grape cultivars Cabernet sauvignon is important because it varies according to the production area. In this work, it was evaluated the content of phenolic compounds and the total antioxidant capacity (CAT) of grape skins and grape seed Cabernet sauvignon (Vitis vinifera L.) in three vineyards located in the Valley of Guadalupe, B.C, México. The content of total phenols was determined by the Folin-Ciocalteau method and the CAT of grape skin and seed extracts by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
4
8
1
Order By: Relevance
“…Furthermore, pulp extract of Horoz Karası was determined to have the highest total phenolic (6.92 μg/mg) and flavonoid (2.18 μg/mg) contents among the studied pulp extracts. In conclusion, total phenolic content of the studied seed extracts were richer than the pulp and leaf extracts that is in parallel with the literature [24,25] …”
Section: Resultssupporting
confidence: 87%
“…Furthermore, pulp extract of Horoz Karası was determined to have the highest total phenolic (6.92 μg/mg) and flavonoid (2.18 μg/mg) contents among the studied pulp extracts. In conclusion, total phenolic content of the studied seed extracts were richer than the pulp and leaf extracts that is in parallel with the literature [24,25] …”
Section: Resultssupporting
confidence: 87%
“…Total phenolic (Özcan et al, 2017). Our findings related to total phenol, total flavonoid and antioxidant activity of grape seeds were higher than the studies of Göktürk Baydar et al (2011), Özcan et al (2017) and Castro-Lopez et al (2019). When results compared to previous studies, some differences observed can be probably attributed to varieties, color of grapes and cultivars and cultural factors.…”
Section: Re Sults and Di̇scussi̇oncontrasting
confidence: 81%
“…(2017) and Castro‐Lopez et al. (2019). When results compared to previous studies, some differences observed can be probably attributed to varieties, color of grapes and cultivars and cultural factors.…”
Section: Results and Di̇scussi̇onmentioning
confidence: 97%
See 1 more Smart Citation
“…It is known that the presence and the ratio of certain phenolic substances in the composition of the grape is primarily a genetically controlled characteristic in varieties. In recent years, phenolic compounds were asserted as an important quality criterion for grape cultivars, and studies related with the determination of differences between them in terms of production capacity become popular (Rodríguez-Montealegre et al 2006;Lutz et al 2011;Perestrelo et al 2012;Atak and Göksel 2019;Castro-Lopez et al 2019;Colombo et al 2019;Di Lorenzo et al 2019). However, the content is characterized by depending on the climate, soil effects, maturity stage and cultural practices in the cultivation area (Ribéreau-Gayon et al 2000).…”
Section: Introductionmentioning
confidence: 99%